Health insurance in Rural Northern Thailand What is available What would be desirable - Thitiwan Sricharoen; Gertrud Buchenrieder (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2008)
Rural livelihoods are exposed to many risks and thus vulnerable. This contribution analyses the relationship between livelihood risks, particularly health risks, and risk management strategies, especially health insurance. The analysis is based on a 2004-survey in the northern mountainous region of Thailand. The random sample consists of 200 farm households. Among the top-ten risks (81% of respondents mentioned them), three were related to health. Interestingly, the Thai Government already offers a mandatory Universal Health Care Scheme, which provides access to medical care for 30 Baht per visit. 75% of the population is insured under this scheme. Nevertheless, it lacks flexibility for the beneficiaries. For this reason, a Choice Based Conjoint analysis was employed to determine traits of health insurance desirable for the rural poor. The traits considered are the premium, the choice of hospital, and the coverage of the microinsurance police.
Keywords: 330